A double-effect composite passivation agent for passivation of high-load waste glass harmful impurity ions and a passivation method and application thereof
Patent Information
- Application Number
- CN202611029614.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-16
AI Technical Summary
(1)离子态杂质无法去除:物理分选只能分离陶瓷、金属、塑料等宏观杂质,无法去除废玻璃中已以离子形式存在的Fe2O3、Cr2O3、NiO等有害杂质,以及陶瓷碎片引入的过量Al2O3
现有物理分选仅能去除陶瓷、金属等宏观杂质,无法消除废玻璃中以离子形式存在的Fe2O3、Cr2O3、NiO等有害杂质及过量Al2O3的负面影响。本发明提出一种离子络合–晶格占位双效钝化机制,通过向玻璃配合料中添加特定的双效复合钝化剂,从化学层面消除有害杂质离子的负面影响。离子络合作用:稀土氧化物(CeO2、La2O3)与过渡金属有害离子(Fe3+、Cr3+、Ni2+等)形成稳定的无色络合物,屏蔽其可见光吸收,消除着色效应。同时,Ce4+/Ce3+氧化还原对可调节玻璃中Fe2+/Fe3+比例,进一步改善颜色。晶格占位作用:碱土金属氧化物(MgO、BaO)中的Mg2+、Ba2+离子占据玻璃网络结构中的间隙位置,固定有害离子,阻止其在熔体和冷却过程中迁移与聚集。同时,这些离子可补偿杂质离子(如Al3+替代Si4+)引起的网络结构缺陷,提高玻璃的化学稳定性和机械强度。稀土氧化物与碱土金属氧化物联合使用,既从显色源头络合屏蔽有害离子,又从结构层面固定和补偿杂质离子,实现1+1>2的钝化协同效果。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of glass manufacturing technology, specifically to a dual-effect composite passivating agent for passivating harmful impurity ions in high-load waste glass, its passivation method, and its application. Background Technology
[0002] Currently, when producing beer bottles and other glass products from high-volume waste glass (waste glass content ≥85%), the treatment of harmful impurities mainly relies on physical sorting technologies (crushing, magnetic separation, eddy current separation, color sorting, etc.), which have the following fatal flaws: (1) Ionic impurities cannot be removed: Physical sorting can only separate macroscopic impurities such as ceramics, metals, and plastics, but cannot remove harmful impurities such as Fe2O3, Cr2O3, and NiO that already exist in waste glass in ionic form, as well as excess Al2O3 introduced by ceramic fragments. These ionic impurities will dissolve in the glass melt during the glass melting process and cannot be separated by physical methods.
[0003] (2) Large fluctuations in product performance: The impurity content of waste glass from different sources can vary by 3-5 times, resulting in fluctuations in the composition of molten glass exceeding ±2%. This is reflected in the products: the batch-to-batch difference in the impact strength of beer bottles is more than 30%, and the failure rate of thermal stability (thermal shock resistance) exceeds 15%, which seriously affects the stable operation of the filling line.
[0004] (3) Poor color consistency: Fe 3+ To make the glass appear yellowish-green, Cr 3+ Ni produces a green color. 2+ This results in brown spots or patches. Under current technology, the color difference ΔE between beer bottles from the same batch is greater than 5 (the industry typically requires ΔE ≤ 3), which fails to meet beer companies' requirements for consistent packaging appearance.
[0005] (4) High melting energy consumption: Excess Al2O3 (introduced by ceramic fragments) will increase the glass melting temperature by 50-80℃ and extend the glass liquid clarification time by about 30%, significantly increasing the furnace energy consumption and production cost.
[0006] (5) Low product qualification rate: Hard particles (such as chromite), microcracks and uneven composition formed by impurities can lead to an increased rate of bottle breakage during filling and transportation. In actual production, the overall qualification rate is generally lower than 75%, resulting in a large waste of energy and raw materials.
[0007] In summary, existing physical sorting technologies cannot solve the negative effects of ionic harmful impurities in high-load waste glass, and there is an urgent need for a chemical method to passivate impurity ions at the formulation level. Summary of the Invention
[0008] To address the shortcomings of existing technologies, this invention innovatively develops a dual-effect composite passivating agent for the passivation of harmful impurity ions in high-load waste glass, along with its passivation method and application. By adding a specific dual-effect composite passivating agent to the glass batch, the negative impact of harmful impurity ions is eliminated from a chemical perspective.
[0009] To achieve the above objectives, the present invention is implemented through the following technical solution: In a first aspect, the present invention provides a dual-effect composite passivating agent for passivating harmful impurity ions in high-load waste glass, comprising: A rare earth oxide composite component, wherein the rare earth oxide composite component comprises cerium oxide and lanthanum oxide; An alkaline earth metal oxide composite component, wherein the alkaline earth metal oxide composite component comprises magnesium oxide and barium oxide.
[0010] As a further optimization of the present invention, the mass ratio of the rare earth oxide composite component to the alkaline earth metal oxide composite component is (2-8):(5-15).
[0011] As a further optimization of the present invention, the mass ratio of cerium dioxide to lanthanum oxide in the rare earth oxide composite component is (2-3):1; the mass ratio of magnesium oxide to barium oxide in the alkaline earth metal oxide composite component is (3-4):1.
[0012] As a further optimization of the present invention, it also includes a dispersant, wherein the dispersant is borax decahydrate; the mass of the dispersant accounts for 10-15 wt% of the total mass of the dual-effect composite passivating agent.
[0013] As a further optimization of the present invention, the particle size D90 of the dual-effect composite passivating agent is <20μm.
[0014] Secondly, the present invention provides a dual-effect passivation method for high loading of harmful impurity ions in waste glass, comprising the following steps: (1) Pre-treat the waste glass to obtain clean waste glass particles; (2) The clean waste glass particles are mixed with silicon source supplement, flux and calcium source raw materials to obtain basic mixture; (3) Add the dual-effect composite passivating agent and fluxing clarifying agent to the basic mixture, mix evenly and then prepare glass batch material; (4) The glass batch is successively melted, clarified, homogenized, shaped and annealed to obtain passivated glass products.
[0015] As a further optimization of the present invention, in step (1), the pretreatment specifically involves: subjecting the waste glass to three-stage crushing treatments in sequence, namely jaw crushing, hammer crushing, and roller crushing, and then subjecting it to magnetic separation to remove iron, eddy current separation to remove non-ferrous metals, color separation to remove ceramic and stone impurities, and high-pressure water washing, to obtain clean waste glass particles with a particle size of 3-5mm.
[0016] As a further optimization of the present invention, in steps (2) and (3), based on the total mass of the glass batch, the amount of clean waste glass particles is 85-92 wt%; the silicon source supplement is quartz sand, with an addition amount of 3-7 wt%; the flux is soda ash, with an addition amount of 2-4 wt%; the calcium source raw material is limestone, with an addition amount of 1-3 wt%; the flux clarifying agent is sodium sulfate or carbon powder, with an addition amount of 0.3-1.0 wt%; the rare earth oxide composite component is added with an addition amount of 0.2-0.8 wt%; and the alkaline earth metal oxide composite component is added with an addition amount of 0.5-1.5 wt%.
[0017] As a further optimization of the present invention, in step (4), the melting is carried out in a horseshoe flame glass furnace at a melting temperature of 1450-1480℃ for 2-2.5 hours; the clarification temperature is 1400-1430℃ for 1-1.2 hours; the homogenization treatment is carried out in a feed channel with a stirring device at a homogenization temperature of 1380±2℃; the annealing treatment specifically involves sending the formed glass product into an annealing furnace and holding it at 550℃-580℃ for 1.5-2 hours to eliminate residual stress, followed by slow cooling to room temperature.
[0018] Thirdly, the present invention provides an application of the aforementioned dual-effect composite passivating agent or the aforementioned dual-effect passivation method in the preparation of glass products from high-load waste glass recycling.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: Existing physical sorting methods can only remove macroscopic impurities such as ceramics and metals, and cannot eliminate the negative effects of harmful impurities such as Fe2O3, Cr2O3, and NiO present in ionic form in waste glass, as well as the negative impact of excess Al2O3. This invention proposes an ion complexation-lattice occupancy dual-effect passivation mechanism. By adding a specific dual-effect composite passivating agent to the glass batch, the negative impact of harmful impurity ions is eliminated at the chemical level. Ion complexation effect: rare earth oxides (CeO2, La2O3) and harmful transition metal ions (Fe2O3, Cr2O3, NiO) interact. 3 + Cr 3+ Ni 2+ (etc.) form a stable colorless complex, shielding its visible light absorption and eliminating the coloring effect. Simultaneously, Ce... 4+ / Ce3+ Redox effect on Fe in tunable glass 2+ / Fe 3+ The proportion further improves the color. Lattice occupancy: Mg in alkaline earth metal oxides (MgO, BaO) 2+ Ba 2+ Ions occupy interstitial positions in the glass network structure, fixing harmful ions and preventing their migration and aggregation during melting and cooling. Simultaneously, these ions can compensate for impurity ions (such as Al). 3+ Replacement of Si 4+ This method addresses network structure defects caused by [the formation of] rare earth oxides, thereby improving the chemical stability and mechanical strength of the glass. The combined use of rare earth oxides and alkaline earth metal oxides not only complexes and shields harmful ions at the color development source but also fixes and compensates for impurity ions at the structural level, achieving a passivation synergy effect greater than the sum of its parts (1+1>2). Detailed Implementation
[0020] The technical solution of the present invention will be described in detail and completely below with reference to specific embodiments. After understanding the core technical concept of the present invention, those skilled in the art can make reasonable adjustments and optimizations without departing from the principles and scope of protection of the present invention. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of protection of the present invention.
[0021] The following examples and comparative examples use the same experimental criteria: Raw material standard: The experimental mixed recycled waste glass was used after uniform pretreatment. The pretreatment process was as follows: the recycled waste glass was subjected to three-stage crushing: jaw crusher, hammer crusher, and roller crusher. Then, it was subjected to magnetic separation to remove iron, eddy current separation to remove non-ferrous metals, color sorting to remove ceramic and stone impurities, and high-pressure water washing and drying to obtain clean waste glass particles with a particle size of 3-5mm. Testing showed that the main chemical composition of the clean waste glass particles was: SiO2 70.2wt%, Al2O3 3.8wt%, Fe2O3 0.35wt%, Cr2O3 0.08wt%, CaO 8.5wt%, MgO 1.2wt%, Na2O+K2O 12.5wt%, with the remainder being trace impurities.
[0022] Preparation of dual-effect composite passivating agent: Weigh rare earth oxides, alkaline earth metal oxides and borax decahydrate dispersant according to the set ratio, put them into a planetary ball mill for dry mixing and grinding, control the particle size D90 < 20μm, and obtain a premixed and uniform dual-effect composite passivating agent for later use.
[0023] Process and testing standards: All samples were processed using the same melting, forming and annealing process. Melting was carried out in a small experimental horseshoe flame furnace. 500mL beer bottle samples were prepared using the small-mouth pressure blowing method. After annealing, performance tests were conducted uniformly.
[0024] Impact strength: Tested according to GB / T6552-2015 "Test Method for Impact Resistance of Glass Bottles and Jars", and the average value of 20 samples was taken. Thermal shock resistance: Tested according to GB / T4547-2007 "Test Method for Thermal Shock Resistance and Thermal Shock Durability of Glass Bottles and Jars", and the maximum temperature difference at which the sample did not crack was recorded. Color deviation ΔE: Tested using a spectrophotometer, with a standard colorless soda-lime glass color chart as the reference, and the average value of 10 samples was taken. Melting temperature: The lowest melting temperature at which the glass melts completely and bubbles are essentially eliminated was recorded. Product qualification rate: The percentage of samples with no appearance defects, qualified dimensions, and satisfactory performance after molding and annealing was statistically analyzed, with 200 pieces counted per batch. Batch stability: Five batches of samples were prepared consecutively, and the coefficient of variation (CV) of impact strength was used to characterize the degree of performance fluctuation between batches.
[0025] Example 1 This embodiment provides a dual-effect passivation method for high loading of harmful impurity ions in waste glass, the steps of which are as follows: (1) Based on the total mass of the glass batch, weigh 85wt% of clean waste glass particles, 7wt% of quartz sand, 4wt% of soda ash and 2.37wt% of limestone, put them into a forced mixer and dry mix for 5 minutes to obtain the basic mixture. (2) Add the double-effect composite passivating agent and sodium sulfate fluxing clarifying agent to the basic mixture, and continue mixing for 18 minutes until uniform to obtain the glass batch.
[0026] The total amount of the dual-effect composite passivating agent is 1.13 wt%, comprising 0.2 wt% rare earth oxide composite component, 0.8 wt% alkaline earth metal oxide composite component, and 0.13 wt% borax decahydrate; borax decahydrate accounts for 11.5% of the total mass of the dual-effect composite passivating agent. The mass ratio of cerium dioxide to lanthanum oxide in the rare earth oxide composite component is 2:1; the mass ratio of magnesium oxide to barium oxide in the alkaline earth metal oxide composite component is 3:1; and the amount of sodium sulfate added is 0.5 wt%.
[0027] (3) The glass batch is fed into the horseshoe flame glass furnace and melted at 1450℃ for 2.5h, and then clarified at 1400℃ for 1.2h. The clarified glass liquid enters the material channel with a stirring device, and the homogenization temperature is controlled at 1380±2℃. After sufficient homogenization, it is formed into 500mL beer bottles by small-mouth pressure blowing method.
[0028] (4) The formed glass products are sent into an annealing furnace and kept at 550°C for 2 hours to eliminate residual stress. Then they are slowly cooled to room temperature to obtain passivated glass products.
[0029] Example 2 This embodiment is a preferred embodiment of the present invention, and the steps are as follows: (1) Based on the total mass of the glass batch, weigh 90wt% of clean waste glass particles, 4wt% of quartz sand, 3wt% of soda ash and 1.0wt% of limestone, put them into a forced mixer and dry mix for 5 minutes to obtain the basic mixture. (2) Add the double-effect composite passivating agent and sodium sulfate fluxing clarifying agent to the basic mixture, and continue mixing for 20 minutes until uniform to obtain glass batch.
[0030] The total amount of the dual-effect composite passivating agent is 1.5 wt%, comprising 0.6 wt% rare earth oxide composite component, 0.8 wt% alkaline earth metal oxide composite component, and 0.1 wt% borax decahydrate; borax decahydrate accounts for 10% of the total mass of the dual-effect composite passivating agent. The mass ratio of cerium dioxide to lanthanum oxide in the rare earth oxide composite component is 2:1 (containing 0.4 wt% CeO2 and 0.2 wt% La2O3); the mass ratio of magnesium oxide to barium oxide in the alkaline earth metal oxide composite component is 3:1 (containing 0.6 wt% MgO and 0.2 wt% BaO); and the amount of sodium sulfate added is 0.5 wt%.
[0031] (3) The glass batch is fed into the horseshoe flame glass furnace and melted at 1470℃ for 2.2h, and then clarified at 1420℃ for 1.1h. The clarified glass liquid enters the material channel with a stirring device, and the homogenization temperature is controlled at 1380±2℃. After sufficient homogenization, it is formed into 500mL beer bottles by small-mouth pressure blowing method.
[0032] (4) The formed glass products are sent into an annealing furnace and kept at 565°C for 1.8 hours to eliminate residual stress. Then they are slowly cooled to room temperature to obtain passivated glass products.
[0033] Example 3 This embodiment verifies the passivation effect at the highest waste glass content, and the steps are as follows: (1) Based on the total mass of the glass batch, weigh 92wt% of clean waste glass particles, 3wt% of quartz sand, 2wt% of soda ash and 0.97wt% of limestone, put them into a forced mixer and dry mix for 5 minutes to obtain the basic mixture. (2) Add the dual-effect composite passivator and carbon powder fluxing clarifying agent to the basic mixture, and continue mixing for 15 minutes until uniform to obtain the glass batch.
[0034] The total amount of the dual-effect composite passivator is 1.73 wt%, comprising 0.8 wt% rare earth oxide composite component, 0.75 wt% alkaline earth metal oxide composite component, and 0.18 wt% borax decahydrate; borax decahydrate accounts for 10.4% of the total mass of the dual-effect composite passivator. The mass ratio of cerium dioxide to lanthanum oxide in the rare earth oxide composite component is 2:1; the mass ratio of magnesium oxide to barium oxide in the alkaline earth metal oxide composite component is 3:1; and the amount of carbon powder added is 0.3 wt%.
[0035] (3) The glass batch is fed into the horseshoe flame glass furnace and melted at 1480℃ for 2 hours, and then clarified at 1430℃ for 1 hour. The clarified glass liquid enters the material channel with a stirring device, and the homogenization temperature is controlled at 1380±2℃. After sufficient homogenization, it is formed into 500mL beer bottles by small-mouth pressure blowing method.
[0036] (4) The formed glass products are sent into an annealing furnace and held at 580°C for 1.5 hours to eliminate residual stress. Then they are slowly cooled to room temperature to obtain passivated glass products.
[0037] Comparative Example 1 This comparative example does not add any dual-effect composite passivating agent or dispersant, and the rest is the same as in Example 2, and a control glass product is prepared.
[0038] Comparative Example 2 This comparative example only added rare earth oxide composite components and borax decahydrate, without adding alkaline earth metal oxide composite components; the rest remained the same as in Example 2, and a control glass product was prepared.
[0039] Comparative Example 3 This comparative example only added alkaline earth metal oxide composite components and borax decahydrate, without adding rare earth oxide composite components; the rest remained the same as in Example 2, and a control glass product was prepared.
[0040] Comparative Example 4 In this comparative example, the rare earth oxide composite component was added at 1.2 wt%, exceeding the upper limit of 0.2~0.8 wt%; the alkaline earth metal oxide composite component was added at 0.5 wt%, which is within the range of 0.5~1.5 wt% as defined in the claims; borax decahydrate was added at 10% of the total mass of the passivating agent, and the rest remained the same as in Example 2, thus preparing the control glass product.
[0041] Comparative Example 5 In this comparative example, the mass ratio of cerium dioxide to lanthanum oxide in the rare earth oxide composite component was adjusted to 1:1. The total amount of rare earth components added was the same as in Example 2 (0.6 wt%). The alkaline earth metal oxide components and their amounts, as well as the amount of dispersant, were the same as in Example 2. The remaining formulation composition and process parameters were the same as in Example 2, and a control glass product was prepared.
[0042] The performance test results of all embodiments and comparative examples are shown in Table 1 below.
[0043] Table 1
[0044] Comparing Example 2 with Comparative Examples 1, 2, and 3, it is evident that using rare earth oxides alone can only improve color through complexation, but the improvement in glass mechanical strength and melting efficiency is limited, with impact strength only increasing by 8.4% compared to the blank group. Using alkaline earth metal oxides alone can only reinforce the structure through lattice occupancy, but cannot effectively eliminate impurities and coloration, resulting in a color deviation as high as 5.1, which fails to meet the appearance requirements of high-end products. However, Example 2 of this invention, which combines rare earth oxides and alkaline earth metal oxides in a specific ratio, shows a 28.4% increase in impact strength, a 21.2% increase in thermal shock temperature difference, a 71.0% reduction in color deviation, a 60°C reduction in melting temperature, a 75.0% reduction in inter-impact strength difference, and a 23.6% increase in product qualification rate compared to the blank Comparative Example 1. The improvement in all indicators is significantly higher than that of the two single components, fully demonstrating the synergistic effect of the dual-effect mechanism of ion complexation decolorization and lattice occupancy reinforcement.
[0045] By comparing Example 2 with Comparative Examples 4 and 5, it can be seen that when the mass ratio of rare earth to alkaline earth significantly exceeds the range of (2-8):(5-15) defined in this invention, even with a significant increase in the amount of rare earth oxides added, a better passivation effect cannot be obtained; the impact strength, thermal shock stability, and product qualification rate all show a significant decline, batch stability deteriorates, melting temperature rises, and only the color index is slightly improved but far from reaching the optimal level. This result shows that there is a strict matching range between the complexing effect of rare earth components and the occupancy effect of alkaline earth components, and the effect is not necessarily better the higher the amount added; the range of the two-component ratio and the internal compounding ratio defined in this invention are the key parameter combinations for achieving synergistic gains.
[0046] In existing technologies, product performance drops sharply when the waste glass content exceeds 70%. However, in Example 3 of this invention, even with a waste glass content as high as 92wt%, excellent comprehensive performance is still maintained, with a product qualification rate of 86% and a color difference ΔE < 2.5. This completely breaks through the industry's technical bottleneck, realizes high-quality and high-proportion resource utilization of waste glass, and has significant practical value.
[0047] The above are merely preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be considered as limitations on the present invention, and the scope of protection of the present invention should be determined by the scope defined in the claims. For those skilled in the art, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A dual-effect composite passivating agent for passivating harmful impurity ions in high-load waste glass, characterized in that, include: A rare earth oxide composite component, wherein the rare earth oxide composite component comprises cerium oxide and lanthanum oxide; An alkaline earth metal oxide composite component, wherein the alkaline earth metal oxide composite component comprises magnesium oxide and barium oxide.
2. The dual-effect composite passivating agent according to claim 1, characterized in that, The mass ratio of the rare earth oxide composite component to the alkaline earth metal oxide composite component is (2-8):(5-15).
3. The dual-effect composite passivating agent according to claim 1 or 2, characterized in that, The mass ratio of cerium dioxide to lanthanum oxide in the rare earth oxide composite component is (2-3):1; the mass ratio of magnesium oxide to barium oxide in the alkaline earth metal oxide composite component is (3-4):
1.
4. The dual-effect composite passivating agent according to claim 1, characterized in that, It also includes a dispersant, which is borax decahydrate; the mass of the dispersant accounts for 10-15 wt% of the total mass of the dual-effect composite passivating agent.
5. The dual-effect composite passivating agent according to claim 1, characterized in that, The particle size D90 of the dual-effect composite passivating agent is <20 μm.
6. A dual-effect passivation method for high loading of harmful impurity ions from waste glass, characterized in that, Includes the following steps: (1) Pre-treat the waste glass to obtain clean waste glass particles; (2) The clean waste glass particles are mixed with silicon source supplement, flux and calcium source raw materials to obtain basic mixture; (3) Add the dual-effect composite passivating agent and fluxing clarifying agent according to any one of claims 1-5 to the basic mixture, and mix them evenly to obtain the glass batch material; (4) The glass batch is successively melted, clarified, homogenized, shaped and annealed to obtain passivated glass products.
7. The dual-effect passivation method according to claim 6, characterized in that, In step (1), the pretreatment specifically involves: subjecting the waste glass to three-stage crushing processes, namely jaw crushing, hammer crushing, and roller crushing, followed by magnetic separation to remove iron, eddy current separation to remove non-ferrous metals, color separation to remove ceramic and stone impurities, and high-pressure water washing, to obtain clean waste glass particles with a particle size of 3-5mm.
8. The dual-effect passivation method according to claim 6, characterized in that, In steps (2) and (3), based on the total mass of the glass batch, the amount of clean waste glass particles is 85-92 wt%; the silicon source supplement is quartz sand, with an addition amount of 3-7 wt%; the flux is soda ash, with an addition amount of 2-4 wt%; the calcium source raw material is limestone, with an addition amount of 1-3 wt%; the flux clarifier is sodium sulfate or carbon powder, with an addition amount of 0.3-1.0 wt%; the rare earth oxide composite component is added at 0.2-0.8 wt%; and the alkaline earth metal oxide composite component is added at 0.5-1.5 wt%.
9. The dual-effect passivation method according to claim 6, characterized in that, In step (4), the melting is carried out in a horseshoe flame glass furnace at a melting temperature of 1450-1480℃ for 2-2.5 hours; the clarification temperature is 1400-1430℃ for 1-1.2 hours; the homogenization treatment is carried out in a feed channel with a stirring device at a homogenization temperature of 1380±2℃; the annealing treatment specifically involves sending the formed glass product into an annealing furnace and holding it at 550℃-580℃ for 1.5-2 hours to eliminate residual stress, followed by slow cooling to room temperature.
10. The application of the dual-effect composite passivating agent according to any one of claims 1-5 or the dual-effect passivation method according to any one of claims 6-9 in the preparation of glass products from high-load waste glass recycling.